Electromigrated electrical optical antennas for transducing electrons and photons at the nanoscale - Dasgupta, Arindam; Buret, Mickaël; Cazier, Nicolas; Mennemanteuil, Marie-Maxime; Chacon, Reinaldo; Hammani, Kamal; Weeber, Jean-Claude; Arocas, Juan; Markey, Laurent; des Francs, Gérard Colas; Uskov, Alexander; Smetanin, Igor; et al. (Beilstein Journal of Nanotechnology, 2018)
Background: Electrically controlled optical metal antennas are an emerging class of nanodevices enabling a bilateral transduction between electrons and photons. At the heart of the device is a tunnel junction that may either emit light upon injection of electrons or generate an electrical current when excited by a light wave. The current study explores a technological route for producing these functional units based upon the electromigration of metal constrictions.Results: We combine multiple nanofabrication steps to realize in-plane tunneling junctions made of two gold electrodes, separated by a sub-nanometer gap acting as the feedgap of an optical antenna. We electrically characterize the transport properties of the junctions in the light of the Fowler–Nordheim representation and the Simmons model for electron tunneling. We demonstrate light emission from the feedgap upon electron injection and show examples of how this nanoscale light source can be coupled to waveguiding structures.Conclusion: Electromigrated in-plane tunneling optical antennas feature interesting properties with their unique functionality enabling interfacing electrons and photons at the atomic scale and with the same device. This technology may open new routes for device-to-device communication and for interconnecting an electronic control layer to a photonic architecture.
Keywords: electromigration; Fowler–Nordheim; hot-electron emission; inelastic electron tunneling; optical antennas; transition voltage; tunnel junction

(untitled) - Roelkens, G.; Liu, L.; Liang, D.; Jones, R.; Fang, A.; Koch, B.; Bowers, J. (Laser Photonics Rev., 2010)

(untitled) - Liu, L.; Roelkens, G.; van Campenhout, J.; Brouckaert, J.; van Thourhout, D.; Baets, R. (J. Nanosci. Nanotechnol., 2010)

2009 3rd ACM/IEEE International Symposium on Networks-on-Chip - Carloni, L. P.; Pande, P.; Xie, Y. (Networks-on-chip in emerging interconnect paradigms: Advantages and challenges, 2009)

(untitled) - Deb, S.; Ganguly, A.; Pande, P. P.; Belzer, B.; Heo, D. (IEEE J. Emerging Sel. Top. Circuits Syst., 2012)

(untitled) - Matolak, D. W.; Kodi, A.; Kaya, S.; Ditomaso, D.; Laha, S.; Rayess, W. (IEEE Wireless Commun., 2012)

2013 IEEE 56th International Midwest Symposium on Circuits and Systems (MWSCAS) - Kaya, S.; Laha, S.; Kodi, A.; Ditomaso, D.; Matolak, D.; Rayess, W. (On ultra-short wireless interconnects for NoCs and SoCs: Bridging the ‘THz Gap’, 2013)

(untitled) - Alù, A.; Engheta, N. (Phys. Rev. Lett., 2010)

(untitled) - Bharadwaj, P.; Deutsch, B.; Novotny, L. (Adv. Opt. Photonics, 2009)

(untitled) - Novotny, L.; van Hulst, N. (Nat. Photonics, 2011)

(untitled) - Mühlschlegel, P.; Eisler, H.-J.; Martin, O. J. F.; Hecht, B.; Pohl, D. W. (Science, 2005)

(untitled) - Gérard, D.; Wenger, J.; Devilez, A.; Gachet, D.; Stout, B.; Bonod, N.; Popov, E.; Rigneault, H. (Opt. Express, 2008)

(untitled) - Schuller, J. A.; Brongersma, M. L. (Opt. Express, 2009)

(untitled) - Alù, A.; Engheta, N. (Phys. Rev. Lett., 2008)

(untitled) - Huang, C.; Bouhelier, A.; Colas des Francs, G.; Bruyant, A.; Guenot, A.; Finot, E.; Weeber, J.-C.; Dereux, A. (Phys. Rev. B, 2008)

(untitled) - Curto, A. G.; Volpe, G.; Taminiau, T. H.; Kreuzer, M. P.; Quidant, R.; van Hulst, N. F. (Science, 2010)

(untitled) - Pavlov, R. S.; Curto, A. G.; van Hulst, N. F. (Opt. Commun., 2012)

(untitled) - Prangsma, J. C.; Kern, J.; Knapp, A. G.; Grossmann, S.; Emmerling, M.; Kamp, M.; Hecht, B. (Nano Lett., 2012)

(untitled) - Buret, M.; Uskov, A. V.; Dellinger, J.; Cazier, N.; Mennemanteuil, M.-M.; Berthelot, J.; Smetanin, I. V.; Protsenko, I. E.; Colas-des-Francs, G.; Bouhelier, A. (Nano Lett., 2015)

(untitled) - Kern, J.; Kullock, R.; Prangsma, J.; Emmerling, M.; Kamp, M.; Hecht, B. (Nat. Photonics, 2015)

(untitled) - Parzefall, M.; Bharadwaj, P.; Jain, A.; Taniguchi, T.; Watanabe, K.; Novotny, L. (Nat. Nanotechnol., 2015)

(untitled) - Gurunarayanan, S. P.; Verellen, N.; Zharinov, V. S.; James Shirley, F.; Moshchalkov, V. V.; Heyns, M.; Van de Vondel, J.; Radu, I. P.; Van Dorpe, P. (Nano Lett., 2017)

(untitled) - Guhr, D. C.; Rettinger, D.; Boneberg, J.; Erbe, A.; Leiderer, P.; Scheer, E. (Phys. Rev. Lett., 2007)

(untitled) - Ward, D. R.; Hüser, F.; Pauly, F.; Cuevas, J. C.; Natelson, D. (Nat. Nanotechnol., 2010)

(untitled) - Arielly, R.; Ofarim, A.; Noy, G.; Selzer, Y. (Nano Lett., 2011)

(untitled) - Miskovsky, N. M.; Cutler, P. H.; Mayer, A.; Weiss, B. L.; Willis, B.; Sullivan, T. E.; Lerner, P. B. (J. Nanotechnol., 2012)

(untitled) - Stolz, A.; Berthelot, J.; Mennemanteuil, M.-M.; Colas des Francs, G.; Markey, L.; Meunier, V.; Bouhelier, A. (Nano Lett., 2014)

(untitled) - Du, W.; Wang, T.; Chu, H.-S.; Nijhuis, C. A. (Nat. Photonics, 2017)

(untitled) - Savage, K. J.; Hawkeye, M. M.; Esteban, R.; Borisov, A. G.; Aizpurua, J.; Baumberg, J. J. (Nature, 2012)

(untitled) - Sanders, A.; Bowman, R. W.; Baumberg, J. J. (Sci. Rep., 2016)

(untitled) - Zhu, W.; Esteban, R.; Borisov, A. G.; Baumberg, J. J.; Nordlander, P.; Lezec, H. J.; Aizpurua, J.; Crozier, K. B. (Nat. Commun., 2016)

(untitled) - Beenakker, C. W. J.; Schomerus, H. (Phys. Rev. Lett., 2004)

(untitled) - Zakka-Bajjani, E.; Dufouleur, J.; Coulombel, N.; Roche, P.; Glattli, D. C.; Portier, F. (Phys. Rev. Lett., 2010)

(untitled) - Pierce, D.; Brusius, P. (Microelectron. Reliab., 1997)

(untitled) - Strachan, D. R.; Smith, D. E.; Johnston, D. E.; Park, T.-H.; Therien, M. J.; Bonnell, D. A.; Johnson, A. T. (Appl. Phys. Lett., 2005)

(untitled) - Mennemanteuil, M.-M.; Buret, M.; Cazier, N.; Colas des Francs, G.; Bouhelier, A.; Besbes, M.; Ben-Abdallah, P. (Phys. Rev. B, 2016)

(untitled) - Esen, G.; Fuhrer, M. S. (Appl. Phys. Lett., 2005)

(untitled) - Shi, S.-F.; Xu, X.; Ralph, D. C.; McEuen, P. L. (Nano Lett., 2011)

(untitled) - Ward, D. R.; Halas, N. J.; Natelson, D. (Appl. Phys. Lett., 2008)

(untitled) - Cho, J.; Thompson, C. V. (Appl. Phys. Lett., 1989)

(untitled) - Simmons, J. G. (J. Appl. Phys., 1963)

(untitled) - Mangin, A.; Anthore, A.; Della Rocca, M. L.; Boulat, E.; Lafarge, P. (Phys. Rev. B, 2009)

(untitled) - Mayer, A.; Chung, M. S.; Lerner, P. B.; Weiss, B. L.; Miskovsky, N. M.; Cutler, P. H. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2011)

(untitled) - Brinkman, W. F.; Dynes, R. C.; Rowell, J. M. (J. Appl. Phys., 1970)

(untitled) - Beebe, J. M.; Kim, B.; Gadzuk, J. W.; Daniel Frisbie, C.; Kushmerick, J. G. (Phys. Rev. Lett., 2006)

(untitled) - Frimmer, M.; Puebla-Hellmann, G.; Wallraff, A.; Novotny, L. (Appl. Phys. Lett., 2014)

(untitled) - Bâldea, I. (EPL, 2012)

(untitled) - Sotthewes, K.; Hellenthal, C.; Kumar, A.; Zandvliet, H. J. W. (RSC Adv., 2014)

(untitled) - Wu, K.; Bai, M.; Sanvito, S.; Hou, S. (Nanotechnology, 2013)

(untitled) - Huisman, E. H.; Guédon, C. M.; van Wees, B. J.; van der Molen, S. J. (Nano Lett., 2009)

(untitled) - Vilan, A.; Cahen, D.; Kraisler, E. (ACS Nano, 2013)

(untitled) - Miskovsky, N. M.; Shepherd, S. J.; Cutler, P. H.; Sullivan, T. E.; Lucas, A. A. (Appl. Phys. Lett., 1979)

Quantum Plasmonics - Parzefall, M.; Bharadwaj, P.; Novotny, L. (Antenna-Coupled Tunnel Junctions, 2017)

(untitled) - Lambe, J.; McCarthy, S. L. (Phys. Rev. Lett., 1976)

(untitled) - Vardi, Y.; Cohen-Hoshen, E.; Shalem, G.; Bar-Joseph, I. (Nano Lett., 2016)

(untitled) - Malinowski, T.; Klein, H. R.; Iazykov, M.; Dumas, P. (EPL, 2016)

(untitled) - Kalathingal, V.; Dawson, P.; Mitra, J. (Sci. Rep., 2017)

(untitled) - Sun, Y.; Fan, X. (Anal. Bioanal. Chem., 2011)

(untitled) - Lee, J. P.; Murray, E.; Bennett, A. J.; Ellis, D. J. P.; Dangel, C.; Farrer, I.; Spencer, P.; Ritchie, D. A.; Shields, A. J. (Appl. Phys. Lett., 2017)

(untitled) - Cazier, N.; Buret, M.; Uskov, A. V.; Markey, L.; Arocas, J.; Colas des Francs, G.; Bouhelier, A. (Opt. Express, 2016)

(untitled) - Kischkat, J.; Peters, S.; Gruska, B.; Semtsiv, M.; Chashnikova, M.; Klinkmüller, M.; Fedosenko, O.; Machulik, S.; Aleksandrova, A.; Monastyrskyi, G.; Flores, Y.; Masselink, W. T. (Appl. Opt., 2012)

(untitled) - Choy, J. T.; Bradley, J. D. B.; Deotare, P. B.; Burgess, I. B.; Evans, C. C.; Mazur, E.; Lončar, M. (Opt. Lett., 2012)

(untitled) - Weeber, J.-C.; Hammani, K.; Colas des Francs, G.; Bouhelier, A.; Arocas, J.; Kumar, A.; Eloi, F.; Buil, S.; Quélin, X.; Hermier, J.-P.; Nasilowski, M.; Dubertret, B. (ACS Photonics, 2016)

(untitled) - Guan, X.; Hu, H.; Oxenløwe, L. K.; Frandsen, L. H. (Opt. Express, 2018)

(untitled) - Bernal Arango, F.; Kwadrin, A.; Koenderink, A. F. (ACS Nano, 2012)

(untitled) - Kim, M.-K.; Li, Z.; Huang, K.; Going, R.; Wu, M. C.; Choo, H. (Opt. Express, 2013)

(untitled) - Crosnier, G.; Sanchez, D.; Bouchoule, S.; Monnier, P.; Beaudoin, G.; Sagnes, I.; Raj, R.; Raineri, F. (Nat. Photonics, 2017)

(untitled) - Daveau, R. S.; Balram, K. C.; Pregnolato, T.; Liu, J.; Lee, E. H.; Song, J. D.; Verma, V.; Mirin, R.; Nam, S. W.; Midolo, L.; Stobbe, S.; Srinivasan, K.; et al. (Optica, 2017)

(untitled) - Barthes, J.; Bouhelier, A.; Dereux, A.; Colas des Francs, G. (Sci. Rep., 2013)

(untitled) - Dionne, J. A.; Sweatlock, L. A.; Atwater, H. A.; Polman, A. (Phys. Rev. B, 2006)

(untitled) - Andryieuski, A.; Zenin, V. A.; Malureanu, R.; Volkov, V. S.; Bozhevolnyi, S. I.; Lavrinenko, A. V. (Nano Lett., 2014)

(untitled) - Dasgupta, A.; Mennemanteuil, M.-M.; Buret, M.; Cazier, N.; Colas des Francs, G.; Bouhelier, A. (Nat. Commun., 2018)